2011
DOI: 10.4103/0972-124x.85666
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aspartate aminotransferase in gingival crevicular fluid: A study with initial therapy

Abstract: Background and Objectives:Conventional diagnostic indicators cannot distinguish between disease activity and inactivity but can detect the past tissue destruction. A proper and true periodontal diagnosis is essential in order to have a rational treatment and preventive strategy and to identify sites at risk. The present longitudinal study was designed with an aim to examine the relationship between gingival crevicular fluid (GCF) levels of aspartate aminotransferase (AST) and periodontal disease progression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Our results also coincide with Mehta et al (23) who found similar results as Shimada et al concerning a positive relation between AST and periodontal diseases. We also have shown that there is a statistically significant correlation between mean periodontal probing depth (PPD) and the AST levels in Saliva at baseline (0-weeks) suggesting that during the diseased state, as the mean PPD increases, the mean AST levels in saliva also increase.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also coincide with Mehta et al (23) who found similar results as Shimada et al concerning a positive relation between AST and periodontal diseases. We also have shown that there is a statistically significant correlation between mean periodontal probing depth (PPD) and the AST levels in Saliva at baseline (0-weeks) suggesting that during the diseased state, as the mean PPD increases, the mean AST levels in saliva also increase.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with chronic periodontitis, three months [11] or one month [12], after the basic therapy, there was a decrease in the AST levels in the saliva. Similar results were obtained in the gingival fluid [14]. Results of this study indicate that the mean value of the AST activity in the saliva of patients with AP was reduced two months after the basic and surgical therapy.…”
Section: Discussionsupporting
confidence: 85%
“…et al [9] published the first study that indicated an increase in the AST levels in gingival fluid in dogs during the experimental periodontitis.Since that time, many researchers have found that the AST activity in the saliva is proportionate to the degree of tissue damage during the chronic periodontitis [10,11] and gingivitis [12]. Due to the pathological process in periodontal tissues, the integrity of the cells is impaired, the permeability of their membranes is disturbed, and thus the AST is increasingly released from the cytoplasm into the saliva.Also, the AST values in the saliva [13] and gingival fluid [14] were in correlation with the values of the CPITN index (Community Periodontal Index of Treatment Needs). Our study has not proved that there is a correlation between the values of clinical parameters and the AST activity in the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain limitations could not be overcome, such as the choice of collection device, length of collection time, number of sample repetitions. [26][27][28] It is a known fact that the amount of GCF collected varies from site to site, and hence the volume collected differs. In this study, we addressed this issue by standardizing the time of collection to 30 seconds, yet the volume of fluid collected differed.…”
Section: Discussionmentioning
confidence: 99%